Diagnosis and Treatment of Low Anterior Resection Syndrome - Masaaki Miyo; Emi Akizuki; Koichi Okuya; Ai Noda; Masayuki Ishii; Ryo Miura; Momoko Ichihara; Maho Toyota; Kohei Okamoto; Tatsuya Ito; Yuji Akiyama; Ichiro Takemasa (Journal of the Anus, Rectum and Colon)
Defecation disorders following rectal resection have long been overlooked as an inevitable surgical complication due to the lack of established diagnostic criteria or definitions. However, these disorders have been recently termed low anterior resection syndrome (LARS), which is a defecation disorder that occurs following rectal resection and impairs the patient's quality of life (QOL). The LARS score developed by Emmertsen et al., which is a patient-reported outcome measure to evaluate the severity of bowel dysfunction following rectal surgery by scoring the major symptoms of LARS, facilitates the diagnosis and assessment of LARS and enables international comparison and validation through the use of validated scores generated according to the international standards. Based on comparisons with other evaluation instruments, the use of the LARS score is strongly recommended internationally for LARS screening in patients following rectal resection. Recent findings have indicated that multiple pathophysiological changes, including reservoir function and evacuation of the neorectum, anal sphincter function, negative impact of a diverting stoma, autonomic denervation, and radiotherapy, are involved in the etiology of LARS. Due to the lack of established treatments and prevention of LARS, a suggested treatment chart for patients with LARS was presented in the Management Guidelines for Low Anterior Resection Syndrome (MANUEL) project. Future surgical treatment should focus not only on the radical cure of cancer and safety of treatment but also on the maintenance and improvement of QOL, with particular attention to the preservation of function. Particularly for rectal cancer, surgeons must formulate treatment plans that consider the prevention and treatment of LARS.